Where Will Women Lawyers Be in 25 Years? - Bivens, Frances E.; Guggenheimer, Joan; Northup, Nancy; Sturm, Susan; Thoyer, Judith Reinhardt (Columbia Journal of Gender and Law, 2003)
Barbara Black said in her unbelievably moving remarks that Columbia has opened up its i nstitutional heart to women.2 I thought that was a wonderful expression and, as a relative newcomer to Columbia, I have to agree. What does this mean? It means that women have become part of the cultural fabric of the Columbia Law School. We are not an accent. We are not an accessory. We are woven into the day-to-day fabric of the school. And this means being able both to participate in the old traditions and to reshape them to make some new traditions and then have that create opportunities for both men and women alike. So, in many ways, this panel is about extending that question to the legal profession as a whole. Are we a part of the profession’s institutional heart? How has this changed? How will we be able to open up the possibility of answering that question for the profession as a whole in the same way that we are beginning to answer it here at Columbia? So this is the panel first where we get to take stock of how the problems facing women have changed; second, where the openings are for institutional responses that respond to the problems facing women in the profession at this point; and finally, where we both would like to be and see ourselves in twenty-five years, in other words, where the profession is going.